2008
DOI: 10.1007/s11249-008-9319-0
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics in the Bridged State of a Magnetic Recording Slider

Abstract: A novel region of tribological interaction is explored by inducing near contact between the magnetic recording slider and disk. In this study, we performed frictional measurements over a wide range of subambient air pressure and disk rotation rate. Since the slider is supported over the disk by an air bearing, it has been found that cycling from ambient to subambient and then back up to ambient pressure over several minutes of time forms a frictional hysteresis loop. The high-friction branch of the loop, refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…The curves of friction force as a function of load force at , and nm obviously agreed with themselves and the repeatability of the measurement was confirmed from this figure. The relationship between the two forces can also be described by (2), which is derived from the JKR model, and (3), which defines the friction force…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The curves of friction force as a function of load force at , and nm obviously agreed with themselves and the repeatability of the measurement was confirmed from this figure. The relationship between the two forces can also be described by (2), which is derived from the JKR model, and (3), which defines the friction force…”
Section: Resultsmentioning
confidence: 99%
“…Thomas et al measured the tribological interaction by inducing near contact between the magnetic recording slider and the disk [2]. They observed that there is a sudden transition to high friction and vibration (bridged state) at some low touchdown pressure when the ambient pressure is decreased, with the magnetic recording slider initially flying over the lubricated disk surface.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we must better understand and accurately measure the friction and adhesion properties of the lubricant films at small scales. The friction properties at a small scale have thus far been usually discussed on the basis of measurements obtained using a surface force apparatus (SFA) or an atomic force microscope (AFM). Brunner et al discussed the relationship between the adhesive force and the surface energy on the magnetic disk surfaces having a PFPE lubricant film by AFM force curve measurements . They reached an interesting conclusion that the adhesive force was proportional to the surface energy.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental evidence of the formation of a macroscopic lubricant bridge between the head surface and the spinning disk was also reported in some papers [21,22]. The lubricant pickup and transfer to the head surface caused by van der Waals forces have been big obstacles to achieving a smaller flying height [23,24].…”
Section: Surface Force Models and Assumptions For Numerical Analysismentioning
confidence: 85%